The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00264-014-2543-3
|View full text |Cite
|
Sign up to set email alerts
|

Should hip fractures be operated upon only by specialist hip unit surgeons in order to lower rates of surgical site infection?

Abstract: Since there were no differences in the SSI outcome between surgeons working in a specialist hip unit and the general orthopaedic surgeons, delaying operative treatment for hip fractures to enable treatment in such a unit or creating a new unit of this type is not necessary. In this respect, the only significant variable is the patient's age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 19 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Further studies showed that surgeons with a low volume of surgeries tend to have higher infection rates 14 (potentially resulting from increased surgical duration). Another study found no difference in hip fracture surgery outcome between a specialist hip unit and a general orthopedic surgeon 15.…”
Section: Discussionmentioning
confidence: 96%
“…Further studies showed that surgeons with a low volume of surgeries tend to have higher infection rates 14 (potentially resulting from increased surgical duration). Another study found no difference in hip fracture surgery outcome between a specialist hip unit and a general orthopedic surgeon 15.…”
Section: Discussionmentioning
confidence: 96%